Risk Mitigation of Workplace Accidents in Oil Palm Plantations Using the HIRADC and FTA Approaches (Case Study: PT. XYZ) - Nur Rachmawati Sutriono Putri; Muhammad Nur; Suherman Suherman; Nazaruddin Nazaruddin; Muhammad Isnaini Hadiyul Umam (Institut Teknologi Adhi Tama Surabaya, 2025)
This study addresses the mitigation of occupational accident risks in oil palm plantations using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) and Fault Tree Analysis (FTA) approaches. A case study was conducted at PT. XYZ with the aim of identifying potential hazards, assessing risk levels, and determining effective control measures to reduce workplace accidents. The HIRADC method was used to identify and assess the risk levels of various work activities in the plantation, while FTA was applied to analyze the root causes of workplace accidents in depth. The results of the study indicate that the main hazards in the plantation include the use of heavy equipment, contact with chemicals, and hazardous environmental conditions. The proposed mitigation measures include safety training, the use of appropriate personal protective equipment (PPE), and enhanced supervision in operational procedures. The implementation of HIRADC and FTA has proven effective in significantly reducing the level of workplace accident risks.